Are switchbacks signatures of magnetic flux ropes generated by interchange reconnection in the corona? - Drake,JF; Agapitov,O; Swisdak,M; Badman,ST; Bale,SD; Horbury,TS; Kasper,JC; MacDowall,RJ; Mozer,FS; Phan,TD; Pulupa,M; Szabo,A; et al. (Astronomy and Astrophysics: a European journal, 2021)
The structure of magnetic flux ropes injected into the solar wind duringreconnection in the coronal atmosphere is explored with particle-in-cellsimulations and compared with {\it in situ} measurements of magnetic"switchbacks" from the Parker Solar Probe. We suggest that multi-x-linereconnection between open and closed flux in the corona will inject flux ropesinto the solar wind and that these flux ropes can convect outward over longdistances before disintegrating. Simulations that explore the magneticstructure of flux ropes in the solar wind reproduce key features of the"switchback" observations: a rapid rotation of the radial magnetic field intothe transverse direction (a consequence of reconnection with a strong guidefield); and the potential to reverse the radial field component. The potentialimplication of the injection of large numbers of flux ropes in the coronalatmosphere for understanding the generation of the solar wind is discussed.